Some socio-economic drivers of agroforestry adoption in Temiyotta Location, Nakuru County, Kenya (Journal of Sustainability, Environment and Peace, 2019)
This paper provides empirical evidence of some socio-economic drivers of adoption of agroforestry practices among small scale farmers in Temiyotta Location, Nakuru County, Kenya. A stratified random sampling procedure was used to select 86 household heads from the three Sub-locations making up the study area, namely Ikumbi, Murginye, and Cheptagum. Primary data were collected from the field using questionnaires, photography, and observation. Secondary data were obtained from published and unpublished sources. Data analysis was carried out using both descriptive and inferential data tools. Research results indicate farm size, household annual income, and household size as the key drivers of agroforestry adoption in the study area. There was no significant statistical relationship between the education level of the household head and adoption of agroforestry practices. It is concluded that socio-economic factors do influence agroforestry adoption in the study area and must, therefore, be incorporated into any interventions meant to enhance agroforestry adoption and diffusion.
Keywords: Agroforestry; adoption; sustainable land management; socio-economic drivers; livelihoods